Balinese Statue Image Classification Using Transfer Learning: A Comparative Study of MobileNetV3 and EfficientNetV2 - Wulandari, Dwi; Iswara, Ida Bagus Ary Indra; Yudi Antara, I Gede Made; Putra Asana, I Made Dwi; Gandika Supartha, I Kadek Dwi (Jurnal Teknik Informatika (Jutif), 2026)
Balinese sculpture is an important form of cultural heritage that exhibits high visual diversity in terms of shape, structure, and carving style, which makes manual identification and documentation challenging. Previous studies on automated statue classification have generally focused on limited sculpture categories and therefore do not fully represent the visual diversity of Balinese sculptures. This study aims to develop an automatic image classification model capable of recognizing multiple Balinese statue categories using transfer learning and fine-tuning strategies. The proposed approach compares two convolutional neural network architectures, MobileNetV3 and EfficientNetV2, across eight statue classes: Dewa, Dewi, Mitologi, Penabuh, Pengapit, Punakawan, Raksasa, and Wanara. A dataset of 8,400 images was constructed from three-dimensional video documentation to capture multiple viewing angles of each statue. The images were processed through frame extraction, resizing, normalization, data augmentation, and dataset splitting. Model training was conducted in two stages, consisting of transfer learning followed by fine-tuning using reduced learning rates. Experimental results indicate that both models achieve high classification performance on the test dataset. MobileNetV3 obtained the highest test accuracy of 99.64% with a loss value of 0.0119, while EfficientNetV2 achieved an accuracy of 98.56% with a loss of 0.0613. These findings demonstrate that lightweight architectures can deliver competitive performance when supported by appropriate training strategies. This study provides a comparative evaluation of efficient deep learning models for cultural heritage image classification and supports the development of more reliable and systematic digital documentation of Balinese sculptures.